2021
DOI: 10.35885/ruthenica.2021.31(2).4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism and morphometric analysis of <i>Filopaludina martensi martensi </i>(Gastropoda: Viviparidae)

Abstract: Sexual dimorphism is the condition where individuals of different sex in the same species exhibit different characteristics beyond the differences in their sexual organs. In this study, individuals of a viviparid species Filopaludina martensi from the Kwai Yai River in Kanchanaburi Province (Thailand) were examined for eight shell and operculum characteristics. Sexual differences were observed in size of shell and operculum, with females being larger than males. The results indicated that morphometric analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Although Viviparidae snails are recognised as sexually dimorphic (Baker, 1928;Thiele, 1929;Brandt, 1974;Tarbsripair, 1998), F. m. martensi snails studied here are not sexually dimorphic with males having functional tentacles, and a penis as seen in the copulat-ing couple (Figure 3). Female individuals are described to have larger and heavier shells, with body volume relating directly to fecundity (Sawangproh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Viviparidae snails are recognised as sexually dimorphic (Baker, 1928;Thiele, 1929;Brandt, 1974;Tarbsripair, 1998), F. m. martensi snails studied here are not sexually dimorphic with males having functional tentacles, and a penis as seen in the copulat-ing couple (Figure 3). Female individuals are described to have larger and heavier shells, with body volume relating directly to fecundity (Sawangproh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Although earlier studies (Bak-er, 1928;Thiele, 1929) observe sexual dimorphism in the Viviparidae family snails -the right tentacle of males is modified into a copulatory organ (Brandt, 1974;Tarbsripair, 1998), no clear differences are noted in the F. m. martensi snails. However, F. m. martensi female individuals have larger and heavier shells, with body volume relating to fecundity (Sawangproh et al, 2021). Female viviparid snails bear eggs and embryos (0 -14) inside their brood pouch until they are fully developed (Berry, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dimorphism refers to differences in phenotypic traits between males and females within the same species (Shine, 1989) and has been demonstrated in many gastropods and bivalves (e.g. Joaquino et al, 2017;Sawangproh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that GMM has an advantage over earlier methods in capturing shape variation in the family (Minton & Wang, 2011;Moneva et al, 2012). Sexual size differences in viviparid snails have been identified, with females possessing larger shells than males (Jokinen, Guerette & Kortmann, 1982;Brown, Varza & Richardson, 1989;Sawangproh et al, 2021). Shape differences were also revealed, with females having a more globose shell and a wider aperture and body whorl (Moneva et al, 2012;Uvayeva et al, 2021), suggesting the differences allow females to brood embryos more successfully (Minton & Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%